Function and Clinical Symptoms are the Main Factors that Motivate Thoracolumbar Adult Scoliosis Patients to Pursue Surgery. Issue 1 (1st January 2017) - Pizones, Javier; Pérez Martin-Buitrago, Mar; Perez-Grueso, Francisco Javier Sánchez; Vila-Casademunt, Alba; Alanay, Ahmet; Obeid, Ibrahim; Kleinstück, Frank; Acaroglu, Emre R.; Pellisé, Ferran
Abstract : Study Design: A retrospective two-cohort comparative analysis of data collected prospectively in an adult deformity multicenter database. Objective: The aim of this study was to define the radiographic and clinical parameters that motivate adult thoracolumbar (TL) scoliosis patients to undergo surgery. Summary of Background Data: TL curves are a primary concern in adulthood, and it is necessary to establish why patients are motivated to seek surgical intervention. Methods: Patients with only main TL/lumbar (TL/L) idiopathic curves were included, defined as Schwab type L curves and Schwab type D curves in which thoracic curves were <40° and the difference between the TL/L-MT Cobb was ≥15°. Demographic data, health-related quality of life (HRQOL) questionnaires, and 14 different radiological preoperative parameters were assessed. Surgical versus conservative cohorts were compared with the Student t test, Chi-square, and the Mann-Whitney U test. Results: A total of 184 patients met the inclusion criteria. Ninety-four were treated conservatively (C), while 90 underwent surgery (S). No differences were found between groups in terms of demographic or radiographic preoperative data. Age (C: 57.5 ± 18 vs . S: 54.2 ± 18 yr; P  = 0.18), coronal TL/L Cobb (C: 52.3° ± 15 vs . S: 50.6° ± 13; P  = 0.61), and sagittal alignment (SVA C: 3.1 cm ± 5.7 vs . S: 4.9 cm ± 6.4; P  = 0.054) were similar. No differences were found in pelvic parameters (pelvic incidence, pelvic tilt, sacral slope), apical translation, coronal balance, lumbar rotatory subluxation, or lumbar lordosis. However, significant differences were found in HRQOL questionnaires. Surgical patients initially had worse COMI scores (C: 4.6 ± 2.3 vs . S: 6 ± 2.3; P  = 0.001), worse ODI scores (C: 27.7 ± 16 vs . S: 38.9 ± 20; P  = 0.000), worse SF-36 physical (C: 40.9 ± 8.5 vs . S: 36 ± 9.5; P  = 0.001) and mental scores (C: 45.8 ± 12 vs . S: 42.2 ± 11.8; P  = 0.032), and worse SRS-22 scores in all domains with mean values under 3.1 points (range = 2.4–3.1). In both SF-36 physical and SRS-22 function, differences between groups were higher than the minimum clinically important difference. Conclusion: After analyzing a large multicenter database, we found that only clinical factors—particularly function impairment—motivated adult TL scoliosis patients to undergo surgery. Demographic and radiographic parameters did not seem to influence decision-making. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the text